Strengthening the bond with the scientific community: FEBS Open Bio in 2025 - Sara Fuentes; Miguel A. De la Rosa (FEBS Open Bio)
FEBS Open Bio remains dedicated to serving the scientific community by ensuring rapid publication of rigorous science and pioneering initiatives to support researchers. In this editorial, we reflect on a year of achievements, and look forward to the new developments planned for 2025.